Low-dose tacrolimus combined with donor-derived mesenchymal stem cells after renal transplantation: a prospective, non-randomized study - Pan, Guang-hui; Chen, Zheng; Xu, Lu; Zhu, Jing-hui; Xiang, Peng; Ma, Jun-jie; Peng, Yan-wen; Li, Guang-hui; Chen, Xiao-yong; Fang, Jia-li; Guo, Yu-he; Zhang, Lei; et al. (Oncotarget, 2016)
Calcineurin inhibitors, including tacrolimus, are largely responsible for advances in allotransplantation. However, the nephrotoxicity associated with these immunosuppressants impairs patients' long-term survival after renal allograft. Therefore, novel regimens that minimize or even eliminate calcineurin inhibitors could improve transplantation outcomes. In this pilot study, we investigated the use of low-dose tacrolimus in combination with mesenchymal stem cells (MSCs), which are immunosuppressive and prolong allograft survival in experimental organ transplant models. Donor-derived, bone marrow MSCs combined with a sparing dose of tacrolimus (0.04-0.05 mg/kg/day) were administered to 16 de novo living-related kidney transplant recipients; 16 other patients received a standard dose of tacrolimus (0.07-0.08 mg/kg/day). The safety of MSC infusion, acute rejection, graft function, graft survival, and patient survival were evaluated over ≥24 months following kidney transplantation. All patients survived and had stable renal function at the 24 month follow-up. The combination of low-dose tacrolimus and MSCs was as effective as standard dose tacrolimus in maintaining graft survival at least 2 years after transplantation. In addition, both groups had similar urea, urine protein, urinary RBC, urinary WBC, 24-h urine protein, and creatinine clearance rates from 7 days to 24 months after transplantation. Furthermore, no differences in the proportion of lymphocytes, CD19, CD3, CD34, CD38, and natural killer cells were detected between the control and experimental groups. None of the MSC recipients experienced immediate or long-term toxicity from the treatment. This preliminary data suggests that the addition of MSCs permits the use of lower dosages of nephrotoxic calcineurin inhibitors following renal transplantation.